(Z)-1-(3-Mesityl-3-methylcyclobutyl)-2-(morpholin-4-yl)ethanone oxime - Sen, Fatih; Dincer, Muharrem; Cukurovali, Alaaddin; Yilmaz, Ibrahim (Int Union Crystallography, 2011)
In the title compound, C20H30N2O2, the cyclobutane ring is puckered, with a dihedral angle of 19.60 (13)degrees between the two planes. In the crystal, the molecules are linked by intermolecular O-H center dot center dot center dot N and weak C-H center dot center dot center dot O hydrogen bonds, as well as a C-H center dot center dot center dot pi hydrogen-bonding association.
Keywords: Oxiconazole